SCREENING OF SECONDARY METABOLITE PHOTOCHEMICALS EXTRACT 96% LEAF’S MAHKOTA DEWA (PHALERIA MACROCARPA) IN THE COASTAL AREA OF BENGKULU CITY, INDONESIA - Kurnia Dewiani; Riana Versita; Yetti Purnama (Proceeding B-ICON, 2022)
Tropical diseases are infectious diseases that occur in tropical regions. The causes of tropical diseases are various types of infections, ranging from viral, bacterial, and fungal to parasitic infections. The pharmacological treatment implemented. Further, non-pharmacological treatment is widely used, but it has side effects, and the level of danger and risk is much lower than synthetic chemical drugs. Some potential plants in Indonesia have been used for treatment, such as Mahkota Dewa (Phaleria macrocarpa). This plant helps treat microbial infections and menstrual pain, lower blood sugar, prevent the side effects of chemotherapy drugs, and lower blood pressure. The study aims to screen for the phytochemical content of secondary metabolites from the leaves of Mahkota Dewa (Phaleria macrocarpa). The method was the maceration in the BPOM laboratory and the Diploma Program of Pharmacy of The University of Bengkulu. The Mahkota Dewa (Phaleria macrocarpa) contains chemicals known as secondary metabolites. The results of the secondary metabolite screening of the leaves Mahkota Dewa (Phaleria macrocarpa) showed the presence of alkaloid compounds, flavonoids, saponins, tannins, terpenoids, saponins, and tannins. Antibacterials ingredients include flavonoids and saponins, antifungal and antibacterial, with three mechanisms: inhibiting nucleic acid synthesis, inhibiting cytoplasmic membrane function, and inhibiting energy metabolism. The flavonoid compound of the flavone class has the potential as an antibacterial with potent inhibition against Escherichia coli (gram-negative bacteria) and Bacillus subtilis (gram-positive bacteria) because it has an OH group bound to CH. The study concluded that the leaves of Mahkota Dewa (Phaleria macrocarpa) located in the coastal area of Bengkulu city are phenol, alkaloid, flavonoids, saponins, terpenoids, and tannins